2022
DOI: 10.1186/s13052-022-01222-9
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective longitudinal analysis of the effects of postnatal weight gain on the timing and tempo of puberty and menarche in a cohort of Italian girls

Abstract: Objective over the last few decades there has been a progressive decline in the average age of onset of pubertal development stages in both sexes. The increase in the prevalence of childhood obesity seems to play an important role in this phenomenon. Design we undertook a retrospective, longitudinal evaluation of the average age of thelarche and menarche to evaluate the relationship between BMI and weight change during the first years of life and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 27 publications
2
6
0
7
Order By: Relevance
“…In the last decade, the prevalence of overweight (including obesity) and obesity among children and adolescents aged 10-19 years raised significantly to 27-28% and 9-10%, respectively ( 20 ). Lower AAM in obese/overweight girls and remarkable negative correlation of BMI and AAM in our study supports the major influence of obesity on the tempo of puberty, as shown by several others ( 21 , 22 , 23 , 24 ).…”
Section: Discussionsupporting
confidence: 91%
“…In the last decade, the prevalence of overweight (including obesity) and obesity among children and adolescents aged 10-19 years raised significantly to 27-28% and 9-10%, respectively ( 20 ). Lower AAM in obese/overweight girls and remarkable negative correlation of BMI and AAM in our study supports the major influence of obesity on the tempo of puberty, as shown by several others ( 21 , 22 , 23 , 24 ).…”
Section: Discussionsupporting
confidence: 91%
“…It has been suggested that obesity may contribute to an early onset of AAM but the causal association of early menarche with obesity is still disputed in the literature [ 22 ]). While some studies claim that the age of pubertal onset is correlated with BMI [ 11 , 47 ], other studies found no correlation between these variables [ 48 , 49 , 50 ], as we confirmed in this study, or interpreted the increased adiposity as a consequence of sexual maturation in precocious girls [ 48 , 51 ]. According to studies conducted in the US by Lee et al [ 52 ], obesity would simply favor an earlier onset of breast development but not the progression through the later stages of puberty.…”
Section: Discussionsupporting
confidence: 61%
“…The age of sexual maturation seems to have stabilized in the majority of developed countries since at least the 1990s [ 2 , 7 ]. However, taking into account environmental influences (particularly overeating and a sedentary lifestyle), a negative relationship between adiposity indices and the timing of menarche was found: AAM decreases as adiposity increases [ 11 ]. Thus, given the close relationships between nutritional status and the reproductive system, an important issue requiring further investigation is whether the ongoing epidemic of childhood obesity [ 12 , 13 ] will persist in population trends toward the earlier onset of female puberty.…”
Section: Introductionmentioning
confidence: 99%
“…Menarche is commonly used to measure girls' pubertal development. Some authors ( 28 , 29 ) suggested that a higher BMI in childhood is related to an earlier age of menarche. A retrospective longitudinal cohort study in Italy ( 27 ) showed that the variation in BMI between age at thelarche and menarche and the Z-score change between body weight (BW) and BMI at thelarche has a relationship with the pubertal tempo, suggesting that early weight increase between BW and BMI at thelarche also influences the duration of puberty.…”
Section: Discussionmentioning
confidence: 99%